Gestion de la participation et choix de langue en ouverture de réunions plurilingues - Mondada, Lorenza; Oloff, Florence (My University, 2011)
This paper offers a detailed analysis of the opening of an international meeting. English Lingua Franca as the official language of the meeting is actively discussed and negotiated by the participants. The analysis highlights the issues identified by the participants themselves in choosing a linguistic regime for their professional exchanges. The English Lingua Franca regime is aimed at facilitating the participation of some of the participants, but creates problems for others, too. The chairman deals with this situation in an embodied way (through his gaze, gesture, bodily postures, and by the way in which he walks through the room), displaying that he orients to different member categories (such as 'anglophone', 'anglophone who can understand French', 'francophile', etc.) as benefitting from or resisting against the definitive language choice.
Keywords: Analyse conversationnelle; interactions professionnelles; plurilinguisme; code-switching; participation